The Histological Study of the Ileum in the Caucasian Squirrel Sciurus anomalus - Intidhar Mohammed Mnati; Ahmed Mustafa Ahmed; baydaa mutlak (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2022)
The current study was designed to identify the histological composition of the ileum in the Caucasian squirrel Sciurus anomalus. Ten adult squirrels were used for the present study. Animals were anesthetized, anatomized, fixed the study specimens in 10% formalin solution, and conducted a series of histological staining techniques. The ileum consists of four main tunicae represented by mucosa, submucosa, muscularis, and serosa. The tunica mucosa consists of three secondary layers: the epithelial lining layer, lamina propria, and muscularis mucosa. The epithelial lining comprises simple columnar epithelial tissue composed of columnar cells and goblet cells. The lamina propria contains simple straight tubular glands called the intestinal glands or the crypt of Lieberkuhn. The muscularis mucosa is composed of a very thin, single layer of smooth muscle fibers arranged circularly. The submucosa consists of dense connective tissue, while the tunica muscularis appears composed of two layers of smooth muscle fibers. The tunica serosa consists of a loose connective tissue that is covered by a mesothelium.